Footnotes : the Black artists who rewrote the rules of the Great White Way - Gaines, Caseen, 1986- (Sourcebooks, 2021)
"For readers of Hidden Figures and Something Wonderful, Footnotes is the story of New York in the roaring twenties and the first Broadway show with an all-Black cast and creative team to achieve success--and its impact on our popular culture. Amidst a culture actively whitewashing, controlling, or trying to prevent their stories from being told, these artists changed the course of American entertainment. This groundbreaking group of performers and the creators (including composer Eubie Blake and lyricist Noble Sissle) sowed the seeds of the Harlem jazz scene and paved the way for people of color on stage and screen, ultimately leading to productions such as West Side Story, Black Panther, and of course, Hamilton"--